Yield Performance And Quality Of Peashoot Microgreens From Seeds Soaked In Varied Concentrations Of Cacl₂ Utilizing Different Water Types - Lestari, Mahayu Woro; Mardiyani, Siti Amaniyah; Ianah, Dewi; Purkait, Bulbul; Yusup, Muhammad Syaifullah (Universitas Islam Malang, 2025)
Microgreens are small vegetables harvested at young age (7-14 days after planting) and are more nutritious than those harvested in mature stage. The aim of this study is to determine the impact of pre-soaked seed using different concentrations of CaCl2 and watering using different types of water on the yield and quality of micro-green peashoots. This study used factorial randomised design of blocks with two factors. The first factor was the pre- soaked seeds with several concentrations of CaCl2, three levels of 0, 0.5 and 1. The second factor is the difference in the type of water, which is made up of three types ( well water, mineral water and destilled water). The results showed that there was no significant interaction between the treatments on the yield and quality of the micro-greens. Separately, the treatment of pre-soaked seedusing some CaCl2 concentration had a significant effect on the fresh weight per box and on the fresh weight of the shoots. Treatment with 0.5 percent CaCl2 resulted in the best fresh weight per box (160.42 g) and the best weight per microgreen shoots (76.63 g). Microgreens soaked in mineral water had the highest weight of shoots (73.85 g) and the highest of ash content (3.59 mg). The results of the organoleptic test showed that the microgreen peashoot was relatively favored by consumers in terms of taste and color. Based on the results of this study, a pre-planting seed soaking treatment using a 0.5% CaCl2 solution is recommended. Mineral water has good prospects for application in microgreen peashoot cultivation to produce good shoot weight and high fiber and mineral quality.